Effect of the Adiantum capillus Veneris Extract on Bax and Bcl2 Apoptotic Markers of Lung Modulation in Trained Rats and Exposed to Hypoxic Stress - M Yadegari; S Riahy; Sh Mirdar; GhR Hamidian; P Mosadegh zavaragh (Institue of Medicinal Plants, ACECR, 2017)
Background: Apoptosis is a type of programmed cell death that occurs by a series of Intercellular messages under Specific conditions. Objective: The aim of present study was investigat role of the Adiantum capillus veneris extract on modulation of Bax and Bcl2 Apoptotic markers of lung in trained rats and exposed to hypoxic stress. Methods: 14 male Wistar rats were sampels of This study, that were Quite healthy and had no disease history (4 weeks old, 72±9 gr weight) that exposed to hypoxic Environment for 3 weeks after 6 weeks high intensity interval training. Half of the samples were taken 500 ml Adiantum capillus veneris extract Per kilogram of body weight in During exposure to hypoxia environment. Finally, lung tissue was extracted for Immunohistochemical Measurements. Results: Statistical analysis showed that Adiantum capillus veneris extract Consumption for 3 veeks in samples that exposed to hypoxia, Significantly reduced Bax protein Expression of Pulmonary alveolar (P≤0.05). also was observed Adiantum capillus veneris extract Consumption for 3 veeks non Significantly increased Bcl2 protein expression (P> 0.05) and  Significantly reduced Bax /Bcl2 Ratio(P≤0.05). Conclusion: It seems that Adiantum capillus veneris extract, Could possibly modulat Pro-apoptotic and anti-apoptotic proteins expression in pulmonary alveolars that exposed to hypoxic Environment that likely has Considerable effects to Inhibition of lung Pro-apoptotic reactions Due hypoxia.